Teacher Engagement: Confirmatory Factor Analysis (CFA) in Measuring Preschool Teacher Engagement Behaviorally, Emotionally and Cognitively - Indriani Rusydi; Tulus Budi Sulistyo Radikun (Psikostudia : Jurnal Psikologi, 2024)
Currently, student engagement is still a hot topic of discussion.   Previous studies show that students who are involved in the learning process tend to achieve better results. Student engagement in learning cannot be separated from the teacher's involvement in teaching.   This study aims to test the construct validity of the preschool teacher engagement measuring tool in terms of behavior, emotions and cognition developed by Pedler et al. (2020) Participants in this research were early childhood teachers with at least 1 year of teaching experience and numbered around 230 people. The measurement method uses self-report with 4 Likert scales. The total number of question items in this questionnaire is 23.   The data were analyzed using confirmatory factor analysis techniques with STATA version 13 software. Through the confirmatory factor analysis procedure, a Teacher Involvement Scale was obtained that matched the model, namely the Teacher Involvement Scale is a tool for measuring teacher involvement which consists of 3 factors, namely behavioral, emotive and cognitive factors. Apart from that, a shorter number of items was obtained, namely 12 items which also had good internal reliability, overall and for each factor or dimension. Thus, the Teacher Involvement Scale can be used to measure teacher involvement in teaching students in the classroom.Saat ini keterlibatan siswa masih merupakan topik yang hangat diperbincangkan.  Penelitian-penelitian sebelumnya menunjukkan bahwa siswa yang terlibat dalam proses pembelajaran cenderung mencapai hasil yang lebih baik. Keterlibatan siswa dalam belajar tidak terlepas dari keterlibatan gurunya dalam mengajar.  Penelitian ini bertujuan untuk menguji validitas konstruk alat ukur keterlibatan guru prasekolah dari segi perilaku, emosi, dan kognitif  yang dikembangkan oleh Pedler et al. (2020) Partisipan dari penelitian ini adalah guru anak usia dini dengan pengalaman mengajar minimal 1 tahun dan berjumlah sekitar 230 orang. Metode pengukuran menggunakan self-report dengan 4 skala Likert. Total aitem pertanyaan dalam kuisioner ini berjumlah 23 buah.  Data dianalisis menggunakan teknik analisis faktor konfirmatori dengan software STATA versi 13.  Melalui prosedur analisis faktor konfirmatori didapatkan Skala Keterlibatan Guru yang cocok dengan modelnya, yaitu Skala Keterlibatan Guru merupakan alat ukur keterlibatan guru yang terdiri dari 3 faktor, yaitu faktor perilaku, emotif dan kognitif. Selain itu, diperoleh jumlah aitem yang lebih singkat, yaitu berjumlah 12 item yang juga memiliki reliabilitas internal yang baik, secara keseluruhan maupun tiap faktor atau dimensinya. Dengan demikian Skala Keterlibatan Guru dapat digunakan untuk mengukur Keterlibatan Guru dalam mengajar siswa di kelas.